TEACHER'S QUESTIONING STRATEGIES IN JUNIOR HIGH SCHOOL: A CASE STUDY - Suartini, N.K.T.; Wedhanti, N.K; Suprianti, G.A.P. (Universitas Pendidikan Ganesha, 2020)
Since questioning plays an important role in the teaching-learning process, the teachers' questions affect the students' learning motivation, particularly in asking or answering a question. This study was a case study which aimed to find out the types of questioning strategies and types of question used by the English teachers. This study's subject was two English teachers who taught seventh-grade students. The data were collected through a questionnaire (Google Form), and it was verified using the interview guide with teachers. This study showed that teachers used five strategies in applying the question: prompting, probing, redirecting, cold call, and wait. Then, the teachers asked three types of questions: procedural, convergent, and divergent questions. Meanwhile, the teachers mostly asked a procedural question and convergent rather than a divergent question. Furthermore, the teacher was expected to promote divergent questions to involve the students' critical thinking.Keywords : Questioning Strategies, Types of Questions